(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
This paper is devoted to a three-species stochastic competitive system with multiplicative noise. The existence of stochastic traveling wave solution can be obtained by constructing sup/sub-solution and using random dynamical system theory. Furthermore, under a more restrict assumption on the coefficients and by applying Feynman-Kac formula, the upper/lower bounds of asymptotic wave speed can be achieved.